"Stand by me": Unveiling the value of own and others' mental illness - Daniela Andrén (Örebro University School of Business, 2024)
This paper calculates the value of experiencing mental illness, either directly or indirectly through knowing someone near, family, or friends (NFF), who is affected. Using the well-being valuation method, which explores the trade-offs between income and self-reported experiences that maintain life satisfaction unchanged within a representative sample of the Swedish adult population, we found that the annual compensation ranges from 21-26 thousand Euros for those only directly affected to 30-37 thousand Euros for individuals affected both directly and indirectly. These results indicate the relevance of designing healthcare policies for good mental health that take in account both direct and indirect impacts of mental illness, and how mental illness is defined, measured, and discussed in societal and political contexts. Such policies can contribute to effectively address the broader economic and social consequences of mental illness.
Keywords: D60; I10; I18; Z13; 330; mental illness; near family and friends; well-being; well-being valuation method; life satisfaction; Sweden